Two-in-one: inherent anhydrous and water-assisted high proton conduction in a 3D metal-organic framework - Nagarkar, Sanjog S.; Unni, SreeKuttan M.; Sharma, Amitosh; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2014)
The development of solid-state proton-conducting materials with high conductivity that operate under both anhydrous and humidified conditions is currently of great interest in fuel-cell technology. A 3Dmetal-organic framework (MOF) with acid-base pairs in its coordination space that efficiently conducts protons under both anhydrous and humid conditions has now been developed. The anhydrous proton conductivity for this MOF is among the highest values that have been reported for MOF materials, whereas its water-assisted proton conductivity is comparable to that of the organic polymer Nafion, which is currently used for practical applications. Unlike other MOFs, which conduct protons either under anhydrous or humid conditions, this compound should represent a considerable advance in the development of efficient solid-state proton-conducting materials that work under both anhydrous and humid conditions.
Keywords: conducting materials; fuel cells; metal-organic frameworks; porous materials; proton conduction